2016
DOI: 10.2174/1574888x10666150630111618
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ; and Its Ligands: Potential Antitumor Agents in the Digestive System

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is a versatile member of the ligand-activated nuclear hormone receptor superfamily of transcription factors, with expression in several different cell lines, especially in the digestive system. After being activated by its ligand, PPARγ can suppress the growth of oral, esophageal, gastric, colorectal, liver, biliary, and pancreatic tumor cells, suggesting that PPARγ ligand is a potential anticancer agent in PPARγ-expressing tumors. This review highlights key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…4-hydroxy-2-nonenal increase PPAR gene expression and accelerate adiponectin protein degradation in adipocytes [ 65 ]. Peroxisome-proliferator-activated receptors has been also reported to arrest colorectal cancer proliferation [ 66 , 67 ], however it has also been linked to poor outcome in metastatic colorectal cancer (mCRC) [ 68 ]. 4-hydroxy-2-nonenal also upregulates prostaglandin E2 [ 69 ] and cyclooxygenase-2 (COX-2) [ 70 ], two factors associated with high proliferative colorectal cancer [ 71 ].…”
Section: Biologic Performances Of Obesitymentioning
confidence: 99%
“…4-hydroxy-2-nonenal increase PPAR gene expression and accelerate adiponectin protein degradation in adipocytes [ 65 ]. Peroxisome-proliferator-activated receptors has been also reported to arrest colorectal cancer proliferation [ 66 , 67 ], however it has also been linked to poor outcome in metastatic colorectal cancer (mCRC) [ 68 ]. 4-hydroxy-2-nonenal also upregulates prostaglandin E2 [ 69 ] and cyclooxygenase-2 (COX-2) [ 70 ], two factors associated with high proliferative colorectal cancer [ 71 ].…”
Section: Biologic Performances Of Obesitymentioning
confidence: 99%
“…[33][34][35] Some synthetic PPARc ligands, such as rosiglitazone, troglitazone and ciglitazone, inhibit the proliferation of tumour cells and induce tumour cell apoptosis. [36][37][38][39][40] In this study, we found that TNBG-5602 can increase the expression of PPARc at the mRNA and protein levels in vitro and in vivo. Further study found that a PPARc agonist (RSG) can enhance the lipid accumulation of TNBG-5602, while a PPARc inhibitor (T0070907) can reverse the lipid accumulation of TNBG-5602.…”
Section: Discussionmentioning
confidence: 52%
“…It was discovered that overexpression of PPARγ can inhibit cell proliferation and tumour growth, while it is reversed in PPARγ‐silenced cancer cells . Some synthetic PPARγ ligands, such as rosiglitazone, troglitazone and ciglitazone, inhibit the proliferation of tumour cells and induce tumour cell apoptosis …”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is a member of the PPAR family and is expressed in a variety of cancers [129]. Activation of PPARγ regulates the expression of multiple target genes and inhibits the proliferation or migration of tumor cells [130].…”
Section: Discussionmentioning
confidence: 99%